The Use of Audio-Visual Media on Skills and Learning Outcomes of Front Roll in Physical Education Learning in Elementary Schools in Makassar City - Marwah, Marwah; Hudain, Muh. Adnan; Ihsan, Andi; Fahrizal, Fahrizal; Adil, Ahmad (UNIVERSITAS NEGERI MAKASSAR, 2025)
This study aims to describe the application of the Audio Visual Media Use Learning Model to the Skills and Learning Outcomes of the Forward Roll in Physical Education Learning in Elementary Schools in Makassar City. This study uses a quantitative approach to descriptive analysis of the type of research, namely classroom action research (CAR) which is carried out in two cycles. Each cycle includes planning, implementation, observation and reflection. The subjects of this study were 30 students of grade V of SDI Bertingkat Labuang Baji Makassar. The focus of this study is the Application of the Audio Visual Media Use Learning Model and Learning Outcomes to the Forward Roll Skill with the theme of locomotor, non-locomotor and manipulative movements. Data collection techniques used in this study are observation, testing and documentation. Data analysis techniques in this study use quantitative analysis. The results of the study showed a significant increase in the learning outcomes of students of SDI Bertingkat Labuang Baji Makassar in the subject of the combination of locomotor, non-locomotor and manipulative movements in floor gymnastics activities, namely forward rolls with the Application of the Audio Visual Learning Model. In the Pre-cycle, student learning completeness only reached 67%. After the Action in cycle I, the completion increased to 77%, in Cycle 2, the student's learning completion reached 96%, this shows that the Action taken has been effective in improving student learning outcomes.